The development of a 360-degree assessment tool on professionalism for general surgery residency training based on a team assessment of behavior form - Busa, Michael James C.
This study was undertaken to develop a multi-source feedback (360-degree) assessment tool on Professionalism in General Surgery. Specific objectives included: 1. Describe lapses in professional behaviors commonly observed by nurses, students and co-residents among the residents of CVGH and VSMMC. 2. Compare these commonly observed negative professional behaviors by nurses, students and co-residents between the surgical residents of CVGH and that of VSMMC. 3. Describe the currently available tools for evaluating professionalism among surgical residents of CVGH and VSMMC. 4. Develop a tool for assessment of professionalism that integrates the observations of multiple raters which is valid, reliable and feasible. The study used the Research and Development (R & D) research design. Respondents included residents, training officers, nurses and medical interns from Cebu Velez General Hospital (CVGH) and Vicente Sotto Memorial Medical Center (VSMMC). All training officers in surgery in the City of Cebu composed the panel experts who content validated the findings and instruments developed in the study. Findings are as follows: 1. To describe the lapses in professional behaviors, compare this between CVGH and VSMMC and describe the currently available tools, a cross-sectional survey Research and Development design was made. It showed common lapses of professional behavior were related to Relationship with Co-workers, Responsibility and Work habits, bedside decorum / Relationship with patients; Moral/Ethical Values, Study Habits/Commitment to Excellence and that significant differences in reporting of these behaviors were noted between CVGH and VSMMC in the themes of Intellectual Integrity, Moral and Ethical Values, Reliability/Responsibility/Work habits, Study habits/Commitment to Excellence and Relationships with Co-workers. 2. To develop the assessment tool, the Systems Approach Model by Dick, Carey and Carey was used. The developed tool was field test to valid respondent-raters. Validity of the tool was made with Cronbach alpha of 0.842 and Reliability by Pearson correlation with highest of 0.948 with all items significant at a confidence level of 0.05. Ninety-eight percent of the respondent-raters indicated the form was clear and easily understood. It was easy to fill up in 89% and was easy to read in 98% while 95% indicated that it took minimal amount of their time to fill the form. One hundred percent of the respondent raters believed that the feedback from this developed tool will be useful for the residents? improvement while 97% believed the tool can be recommended for use with other departments.